Love, Work, and Striving for the Self in Balance: Anaclitic and Introjective Patients’ Experiences of Change in Psychoanalysis - Werbart, Andrzej; Bergstedt, Annelie; Levander, Sonja (Frontiers in Psychology, 2020)
One of the most famous quotations credited to Freud is that, when asked what he thought a psychological healthy person should be able to do, he had said: “to love and to work.” A central goal in psychoanalytic treatment is to bring about changes in basic, mostly unconscious, mental structures. The aim of this study was to investigate, applying inductive thematic analysis, the experiences of anaclitic and introjective patients, respectively, of change after psychoanalysis with regard to the domains Love and Relationships and Work and Achievements. Analyzing patient interviews, we identified a third domain of experienced changes, The Self, which refers to increased self-understanding, self-acceptance and self-care, rather than improved dynamic balance between love and work. All patients experienced several positive changes in their lives during and after psychoanalysis. We also found distinctive patterns that appear to be closely linked to the patients’ initial personality orientation on relationships or on achievements. Generally, the patients described symmetrical, but opposite, broad change processes within the two specific domains Love and Work. For the anaclitic patients, this indicated a movement inwards in the domain of Love (from an excessive preoccupation with issues of relationship to others toward more distinct self-boundaries and increased agency) and outwards in the domain of Work (from unenterprising towards becoming more outgoing and daring). For the introjective patients this pointed to a reverse movement outwards in the domain of Love (from an excessive preoccupation with issues of autonomy towards increased responsiveness to others and desire to be establish close, mutual relationships) and inwards in the domain of Work (from an excessive orientation on achievements toward increased becoming more grounded in their own feelings, needs and desires). In conclusion, patients in both groups have experienced a reduced preoccupation with issues related to their initially predominant personality dimension (relatedness or self-definition) and increased receptivity to needs typical for the complementary dimension. These changes seem to be mediated by changes in the domain of The Self. Our study suggests the clinical relevance of focusing the therapeutic work on fostering a better and more dynamic balance between love and work, relatedness or self-definition.